2003
DOI: 10.1021/es034801o
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Differences in Cd and Zn Bioaccumulation and Subcellular Storage among Different Populations of Marine Clams

Abstract: The marine clams Mactra veneriformis were collected from three different locations in a contaminated bay in Northern China. Another species of clams Ruditapes philippinarum was collected from the same contaminated bay as well as from a relatively clean site in Hong Kong. The indices of Cd and Zn bioaccumulation (assimilation efficiency, dissolved uptake rate, and efflux rate), tissue concentration, subcellular distribution, metallothionein (MT) content, and clearance rate of the clams were subsequently quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 38 publications
(66 reference statements)
10
48
3
Order By: Relevance
“…It is likely that the induced MT level was still not high enough to affect dietary uptake. The highest MT level in this study was 20.3 ± 9.7 µg g -1 compared to 46.2 ± 5.7 µg g -1 observed for the same species concomitant with an increase in Cd AE (Shi & Wang 2004). However, it has also been suggested that metal AE is not related to MT levels, since repartitioning of metals into MTLP requires a long period of time e.g.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…It is likely that the induced MT level was still not high enough to affect dietary uptake. The highest MT level in this study was 20.3 ± 9.7 µg g -1 compared to 46.2 ± 5.7 µg g -1 observed for the same species concomitant with an increase in Cd AE (Shi & Wang 2004). However, it has also been suggested that metal AE is not related to MT levels, since repartitioning of metals into MTLP requires a long period of time e.g.…”
Section: Discussioncontrasting
confidence: 54%
“…The increase in Cd AEs in green mussels following Cd exposure was mainly attributed to the induction of MT synthesis that sequestered Cd and increased the cytosolic Cd concentration (Blackmore & Wang 2002). Similarly, the higher Cd AE observed in polluted populations of the clams Ruditapes philippinarum and Mactra veneriformis was related to the higher fraction of Cd associated with the MTLP (Shi & Wang 2004). However, in our present study, the Cd AE of clams after Cd preexposure remained unchanged, irrespective of the level of MT synthesis.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Another subsample of pre-exposed fish was dissected into 3 parts (gills, viscera and muscle), and the metallothionein concentrations were measured using a modified silver saturation method (Scheuhammer & Cherian 1991, Shi & Wang 2004. Briefly, the tissues were homogenized in cold 0.25 M sucrose and ultrasonicated.…”
Section: Methodsmentioning
confidence: 99%
“…Prior metal exposure may induce specific metal detoxification processes or physiological and biochemical changes that can subsequently affect the uptake of metals (Wang and Rainbow, 2005). Shi and Wang (2004) compared the cadmium biokinetics in clams Ruditapes philippinarum from a previously contaminated site and a "clean" site and found that the contaminated clam population had a higher metallothionein (MT) concentration compared to the uncontaminated population. No significant difference in the dissolved uptake rate constants, efflux rate constants and the clearance rates of the two were observed between the populations and the contaminated clam population had significantly higher cadmium and zinc AEs compared to the uncontaminated population.…”
Section: Overall Observations On Metals Concentrations Between T ¼ 0 mentioning
confidence: 99%